Correlated disorder-to-order crossover in the local structure of KxFe2-ySe2-zSz - Mangelis, P.; Koch, R. J.; Lei, H.; Neder, Reinhard; Mcdonnell, M. T.; Feygenson, M.; Petrovic, C.; Lappas, A.; Bozin, E. S. (Physical Review B, 2019)
A detailed account of the local atomic structure and disorder at 5 K across the phase diagram of the high-temperature superconductor KxFe2-ySe2-zSz (0 <= z <= 2) is obtained from neutron total scattering and associated atomic pair distribution function (PDF) approaches. Various model-independent and model-dependent aspects of the analysis reveal a high level of structural complexity on the nanometer length scale. Evidence is found for considerable disorder in the c-axis stacking of the FeSe1-xSx slabs without observable signs of turbostratic character of the disorder. In contrast to the related FeCh (Ch = S, Se)-type superconductors, substantial Fe-vacancies are present in KxFe2-ySe2-zSz, deemed detrimental for superconductivity when ordered. Our study suggests that the distribution of vacancies significantly modifies the iron-chalcogen bond-length distribution, in agreement with observed evolution of the PDF signal. A crossoverlike transition is observed at a composition of z approximate to 1, from a correlated disorder state at the selenium end to a more vacancy-ordered (VO) state closer to the sulfur end of the phase diagram. The S-content-dependent measures of the local structure are found to exhibit distinct behavior on either side of this crossover, correlating well with the evolution of the superconducting state to that of a magnetic semiconductor toward the z approximate to 2 end. The behavior reinforces the idea of the intimate relationship of correlated Fe-vacancy order in the local structure and the emergent electronic properties.
CRIS-Team WoS Importer:2019-10-04